Functional neuroimaging predictors of self-reported psychotic symptoms in adolescents - Bourque, Josiane; Spechler, Philip A.; Potvin, Stéphane; Whelan, Robert; Banaschewski, Tobias; Bokde, Arun L.W.; Bromberg, Uli; Büchel, Christian; Quinlan, Erin Burke; Desrivières, Sylvane; Frouin, Vincent; Gowland, Penny (American Psychiatric Publishing, 2017)
OBJECTIVE: This study aimed to investigate the neural correlates of psychotic-like experiences in youth on measures of inhibitory control, reward anticipation and emotion processing. A secondary aim was to test whether these neuro-functional correlates of risk were predictive of psychotic symptoms 2 years later. METHOD: Functional imaging response to three paradigms: the Stop-Signal, Monetary Incentive Delay, and Faces tasks was collected in youth at age 14, as part of the IMAGEN study. At baseline, youth from London and Dublin sites were assessed on psychotic-like experiences and those reporting significant experiences were compared with matched controls. Significant brain activity differences between the groups were used to predict, with cross-validation, the presence of psychotic symptoms in the context of mood fluctuation at age 16, assessed in the full sample. These prediction analyses were conducted with the London-Dublin subsample (N=246) and the full sample (N=1196). RESULTS: Youth reporting psychotic-like experiences showed increased hippocampus/amygdala activity during neutral faces processing and reduced dorsolateral prefrontal activity during failed inhibition relative to controls. The most prominent region for classifying 16-year olds with mood fluctuation and psychotic symptoms relative to the control groups (those with mood fluctuations but no psychotic symptoms and those with no mood symptoms) included hyperactivation of the hippocampus/amygdala, when controlling for baseline psychotic-like experiences and cannabis use. CONCLUSIONS: The results stress the importance of the limbic network’s increased response to neutral facial stimuli as a marker of the extended psychosis phenotype. These findings might help to guide early intervention strategies for at-risk youth.